Problems of Bankruptcy Applications for Solven Companies from the Perspective of Simple Proof and Substantive Justice - Richard Herlambang; Faisal Santiago (Indonesian Journal Publisher, 2026)
The development of bankruptcy practices in Indonesia reveals the emergence of bankruptcy petitions for companies that are still in a state of insolvency, which raises serious questions about the balance between procedural certainty and substantive justice. The simple evidentiary standard as stipulated in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations makes it easier for creditors to file bankruptcy petitions with relatively minimal formal requirements, namely the presence of two creditors and one debt that is due and collectible. This characteristic accelerates the commercial justice process, but at the same time has the potential to create a gap between procedural norms and the economic reality of the debtor. This article aims to analyze the concerns of bankruptcy petitions for solvent companies, identify distortions in the function of bankruptcy as a collective mechanism for resolving insolvency, and formulate a normative reconstruction of a more balanced evidentiary standard. The research method employs normative legal research with statutory, conceptual, case, and comparative approaches. The analysis is conducted on bankruptcy regulations, legal doctrine, and commercial justice practices to assess the tension between legal formalism and substantive justice. The study's findings demonstrate that the dominance of simple evidentiary procedures has the potential to disregard the assessment of real financial conditions, thus opening up the opportunity for bankruptcy to be used as a strategic pressure tool. The proposed normative reconstruction includes the integration of insolvency assessment as an additional parameter, strengthening judicial interpretation guidelines, and reformulating evidentiary standards to accommodate procedural efficiency while more proportionately considering economic implications. This approach is expected to strengthen bankruptcy's function as a fair, rational, and responsive debt resolution mechanism, aligned with the dynamics of the modern business world.